2013
DOI: 10.1080/01634372.2012.728185
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving for Parents and In-Laws: Commonalities and Differences

Abstract: This study examined support, stress, and well-being between adults who provide care for an aging and disabled parent and those who care for an aging and disabled parent-in-law. The study utilized a sample of individuals caring for a parent (n = 77), individuals caring for an in-law (n = 26) and a comparison group of noncaregivers (n = 1,939) from the Midlife Development in the United States study. In-law caregivers provided more financial assistance but adult child caregivers provided more emotional support an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Participants in this study became totally responsible for the care of their parent(s) because of flexibility in work schedule, being childless, or close proximity. 10 Participants missed their normal routine of eating healthy or engaging in regular exercises and became delinquent on scheduled health care appointments. There is evidence showing that self-neglect occurs due to lack of recognition for the extensive caregiving work that is done.…”
Section: Discussionmentioning
confidence: 99%
“…Participants in this study became totally responsible for the care of their parent(s) because of flexibility in work schedule, being childless, or close proximity. 10 Participants missed their normal routine of eating healthy or engaging in regular exercises and became delinquent on scheduled health care appointments. There is evidence showing that self-neglect occurs due to lack of recognition for the extensive caregiving work that is done.…”
Section: Discussionmentioning
confidence: 99%
“…This might be because in such cases the illness of the care recipient is also burdensome. A previous study observed that giving care to a parent was associated with poorer mental health, but giving care to an in-law was not [ 26 ]. It was suggested that this difference is due to type of care provided, with less emotional support and more practical care [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study observed that giving care to a parent was associated with poorer mental health, but giving care to an in-law was not [ 26 ]. It was suggested that this difference is due to type of care provided, with less emotional support and more practical care [ 26 ]. Similarly, we observed a higher risk of emotional disorder when the caregiver provided emotional support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different family members have different types of burdens in caring for family members. Spouses bear greater care and financial burdens [1-3], while adult children provide emotional support and unpaid work [1,4]. In addition, caregiving responsibilities borne by children vary based on gender [5,6].…”
Section: Introductionmentioning
confidence: 99%